Effects of foot intensive rehabilitation (FIRE) on clinical outcomes for patients with chronic ankle instability: a randomized controlled trial protocol - Matthew C. Hoch; Jay Hertel; Phillip A. Gribble; Nicholas R. Heebner; Johanna M. Hoch; Kyle B. Kosik; Doug Long; Pinata H. Sessoms; Amy Silder; Danielle M. Torp; Katherine L. Thompson; John J. Fraser (BMC, 2023)
Abstract Background Lateral ankle sprains account for a large proportion of musculoskeletal injuries among civilians and military service members, with up to 40% of patients developing chronic ankle instability (CAI). Although foot function is compromised in patients with CAI, these impairments are not routinely addressed by current standard of care (SOC) rehabilitation protocols, potentially limiting their effectiveness. The purpose of this randomized controlled trial is to determine if a Foot Intensive REhabilitation (FIRE) protocol is more effective compared to SOC rehabilitation for patients with CAI. Methods This study will use a three-site, single-blind, randomized controlled trial design with data collected over four data collection points (baseline and post-intervention with 6-, 12-, and 24-month follow-ups) to assess variables related to recurrent injury, sensorimotor function, and self-reported function. A total of 150 CAI patients (50 per site) will be randomly assigned to one of two rehabilitation groups (FIRE or SOC). Rehabilitation will consist of a 6-week intervention composed of supervised and home exercises. Patients assigned to SOC will complete exercises focused on ankle strengthening, balance training, and range of motion, while patients assigned to FIRE will complete a modified SOC program along with additional exercises focused on intrinsic foot muscle activation, dynamic foot stability, and plantar cutaneous stimulation. Discussion The overall goal of this trial is to compare the effectiveness of a FIRE program versus a SOC program on near- and long-term functional outcomes in patients with CAI. We hypothesize the FIRE program will reduce the occurrence of future ankle sprains and ankle giving way episodes while creating clinically relevant improvements in sensorimotor function and self-reported disability beyond the SOC program alone. This study will also provide longitudinal outcome findings for both FIRE and SOC for up to two years. Enhancing the current SOC for CAI will improve the ability of rehabilitation to reduce subsequent ankle injuries, diminish CAI-related impairments, and improve patient-oriented measures of health, which are critical for the immediate and long-term health of civilians and service members with this condition. Trial Registration Clinicaltrials.gov Registry: NCT #NCT04493645 (7/29/20).